Pengaruh kondisi sosial ekonomi orang tua terhadap motivasi belajar peserta didik - Monica Siburian; Adeng Hudaya; Bahrudin Salim (Universitas Indraprasta PGRI, 2023)
the research objective was to determine the effect of parents' socio-economic conditions on the learning motivation of class X students at SMA Negeri 96 Jakarta. The method used is a survey method, the approach used is quantitative, by collecting questionnaire data on a population of 208 students, a sample of 67 students. Through the analysis test carried out, the regression equation is Y = 46.705 + 0.516 X with the results of calculating the correlation r of 0.531, which means that there is a moderate relationship between the socio-economic conditions of parents and students' learning motivation. Parents' socio-economic conditions contributed 28.23% to learning motivation and the remaining 71.77% was influenced by other factors. Hypothesis testing obtained ????ℎ???????????????????? = 5.969 > ???????????????????????? = 1.669, meaning that there is influence of parents' socioeconomic conditions on students' learning motivation. Based on these results it can be concluded that there is an influence of parents' socioeconomic conditions on the learning motivation of class X students at SMA Negeri 96 Jakarta.